The influence of children on female wages: Better or worse in Australia? - Hosking, A (My University, 2011)
Studies from the United States and Britain have shown that children influence women’s economic status through a reduction in hours of employment, as well as a decline in hourly wage rates. A substantial portion of this ‘motherhood wage penalty’ has been shown to arise through employment interruptions and spells of part-time employment. This seminar will describe findings from a complementary study of mothers’ wages in Australia. In contrast to the United States and Britain, Australia has historically had a more centralised system of wage determination, lower rates of maternal employment, higher rates of part-time employment and discrimination laws that prohibit job dismissal on the basis of family responsibilities. Some of these factors may have the effect of narrowing the wage penalty for motherhood in Australia, whereas other factors may have the effect of increasing the overall penalty. This seminar will describe findings from a longitudinal analysis of mothers’ wages in Australia using the first six waves of the Household, Income and Labour Dynamics in Australia (HILDA) survey. I will present an updated estimate of the motherhood wage gap in Australia and describe how mothers’ selection out of employment affects this indicator of wage inequality. Next I will describe findings from a regression analysis that shows neither employment interruptions nor part-time working hours can explain the motherhood wage penalty in Australia. In the final part of the seminar, I will summarise findings from a focused analysis of work hours transitions among Australian mothers returning to paid work within three years of a birth event. This analysis will show that the transition from full-time to part-time employment is linked to neither downward occupation mobility nor poorer wage outcomes. Several explanations for the distinctive quality of Australian mothers’ part-time employment will also be discussed.
Keywords: Employment; Families -- Mothers; Finance -- Income (Salary and Wages); Finance; Employment -- Labour force participation; Families; Gender -- Female; Gender; Families and relationships; Income, wealth and finances; Labour market; Employment; Finance; Families; Gender; Mothers; Female; Labour force participation; Income (Salary and Wages); Families and relationships; Income, wealth and finances; Employment and unemployment